Development of a Metastasis-Related Immune Prognostic Model of Metastatic Colorectal Cancer and Its Usefulness to Immunotherapy - Luo, Zhiwen; Chen, Xiao; Zhang, Yefan; Huang, Zhen; Zhao, Hong; Zhao, Jianjun; Li, Zhiyu; Zhou, Jianguo; Liu, Jianmei; Cai, Jianqiang; Bi, Xinyu (Frontiers in Cell and Developmental Biology, 2021)
Post-surgical recurrence of the metastatic colorectal cancer (mCRC) remains a challenge, even with adjuvant therapy. Moreover, patients show variable outcomes. We set to identify gene models based on both intrinsic cell activities and extrinsic immune microenvironment to predict the recurrence of mCRC and guide adjuvant therapy. An RNA-based gene expression analysis of CRC samples (mCRCs=344, non-mCRCs=654) was performed. A metastasis-evaluation model (MEM) for mCRCs was developed using the COX based on the prognostic differentially expressed genes between mCRCs and non-mCRCs. MEM separated the mCRC samples into high- and low-recurrence risk clusters that were tested using machine learning to predict recurrence. Further, an immune prognostic model (IPM) was built using the COX with the prognostic differentially expressed immune-related genes between the two MEM risk clusters. The ability of MEM and IPM to predict prognosis was analyzed and validated. Moreover, the relationship of IPM with immune microenvironment and response to immuno/chemotherapy. A high postoperative recurrence risk was observed owing to the down-regulation of the immune response, which was influenced by MEM genes (BAMBI, F13A1, LCN2) and their related IPM genes (SLIT2, CDKN2A, CLU). MEM and IPM were developed and validated through mCRC samples to differentiate between low and high recurrence risk. The functional enrichment analysis suggested pathways related to immune response and immune system diseases as the major functional pathways related to IPM genes. The IPM high-risk group (IPM-high) had more regulatory T cells, and smaller fractions of resting memory CD4+ T cells than the IPM-low. Moreover, the stroma and immune cells in the IPM-high were scant. Further, the IPM-high showed down-regulation of all MHC class II molecules. Additionally, the TIDE algorithm and GDSC analysis suggested the IPM-low as a promising responder to ICIs, and the targeted drugs, while the IPM-high was non-responsive to these treatments. However, treatment using anti-CDKN2A agents, along with activating MHC class-II response might sensitize this refractory mCRC sub-group. Therefore, the IPM could identify sub-groups of mCRC with a distinct risk of recurrence, and stratify the patients sensitive to immuno/chemotherapy. Further, for the first time, our study highlights the importance of MHC class-II molecules in immunotherapy of mCRC.